1980
DOI: 10.1056/nejm198007243030403
|View full text |Cite
|
Sign up to set email alerts
|

Prediction of BCNU Pulmonary Toxicity in Patients with Malignant Gliomas

Abstract: Symptomatic pulmonary disease occurred in 20 per cent of 93 patients with anaplastic gliomas being treated with carmustine (BCNU). An analysis of the variables has revealed a relation between the occurrence of pulmonary toxicity on the one hand, and the total cumulative dose of BCNU, the number of cycles over which the BCNU was administered, the history of lung disease, the patient's age, and the platelet-count nadir after the first course of BCNU on the other. An equation has been generated that allows predic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
38
0
1

Year Published

1981
1981
2011
2011

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 180 publications
(40 citation statements)
references
References 6 publications
1
38
0
1
Order By: Relevance
“…Follow-up studies in another 10 patients showed a significant sub-clinical deterioration in lung function following chemotherapy (Table V). The clinical, radiological and histological features of 'early onset' lung fibrosis have previously been described with BCNU and other nitrosoureas (Bailey et al, 1978;Durant et al, 1979;Aronin et al, 1980;Sekler et al, 1980;Weiss et al, 1981); correlation is seen when cumulative dosage of BCNU > 1000mgm2 (Weiss et al, 1981). However, the two cases of interstitial pneumonitis in our study received a cumulative dosage of < 400 mg m-2 of fotemustine suggesting that the synergy between DTIC and fotemustine (as used in the schedule here) may be responsible for the acute pulmonary event, possibly related to greater cytotoxicity in normal lung cells following depletion of the endogenous ATase.…”
Section: Discussionmentioning
confidence: 90%
“…Follow-up studies in another 10 patients showed a significant sub-clinical deterioration in lung function following chemotherapy (Table V). The clinical, radiological and histological features of 'early onset' lung fibrosis have previously been described with BCNU and other nitrosoureas (Bailey et al, 1978;Durant et al, 1979;Aronin et al, 1980;Sekler et al, 1980;Weiss et al, 1981); correlation is seen when cumulative dosage of BCNU > 1000mgm2 (Weiss et al, 1981). However, the two cases of interstitial pneumonitis in our study received a cumulative dosage of < 400 mg m-2 of fotemustine suggesting that the synergy between DTIC and fotemustine (as used in the schedule here) may be responsible for the acute pulmonary event, possibly related to greater cytotoxicity in normal lung cells following depletion of the endogenous ATase.…”
Section: Discussionmentioning
confidence: 90%
“…1,500 mg/m 2 . 87 Lung injury may even occur at lower doses in individuals who have previously received thoracic radiation. 86 Symptoms such as dyspnea, tachypnea, and nonproductive cough, may develop as early as 1 month after initiation of therapy.…”
Section: Hsct and Lung Injurymentioning
confidence: 99%
“…Drug-induced pneumonitis has been a well-recognised complication of treatment with BCNU since the 1970s (Collis et al, 1991) and the risk rises steadily with increasing dose (Aronin et al, 1980). Other risk factors are pre-existing lung disease and smoking (Kreisman et al, 1992), although the former just failed to reach statistical significance in the current study.…”
Section: Prognostic Factorsmentioning
confidence: 56%